Iverson, Jennifer. 2018. Electronic Inspirations: Technologies of the Cold-War Musical Avant Garde. New York: Oxford University Press. - Gordon, Ted (Current Musicology, 2019)
Jennifer Iverson’s Electronic Inspirations explores the history of electronic music in the studio of Cologne’s westdeutcher Rundfunk (WDR) in the immediate post-war era, during which elektronische Musik developed as an admixture of music, science, and technology. Iverson shows how elek-tronische Musik inhabited a particular social milieu, including figures like impresario Herbert Eimert, ex-Nazi scientist Walter Meyer-Eppler, and firebrand composers such as Karlheinz Stockhausen, John Cage and David Tudor. As Iverson argues, closely following these actors through the WDR studio illustrates what elektronische Musik meant in cold war Germany: a promise of a better future through what she calls a “reclamation” (2) of the past, achieved through collaborative work between scientists, technicians, musicians, and performers. Through thorough analyses of numerous works produced in the studio, Iverson concludes that these reclamations were ultimately “attempted, incomplete, [and] tenuous”: they failed in achieving their ostensible goal, a “timbral utopia” inhabited by enlightened composers (29). Instead, these reclamations produced what Iverson calls “invisible collaborations,” obscuring the distribution of authorial agency, aesthetic possibilities, and ideological meanings created at the WDR and instead reproducing heroic narratives of “remasculinization” and German musical hegemony (18). Electronic Inspirations illuminates those invisible collaborations through rich and detailed analyses of archival recordings, sketches, concert programs, and planning documents that show exactly how science and technology contributed to the creation of elektronische Musik at the WDR.